Negotiation Competencies Based on Assertiveness and Self Efficacy for Vocational High School Students - Sriyanto, S.; Murniawaty, Indri; Na'imah, Tri (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to determine the association of assertiveness, self efficacy with the competency of negotiations for students. The study was conducted in State Vocational School 1 Bawang Banjarnegara involving 132 samples in Study Program of Online Marketing Business. Sampling technique was stratified random sampling, and data collection technique used questionnaire instruments. Data were analyzed through correlation technique data of product moment. Based on hypothesis testing, results can be obtained that assertiveness had a positive relationship with negotiation competencies. Similarly, self efficacy also had a positive relationship to negotiation competencies; these two independent variables also had a positive and significant relationship to negotiation competencies. The implications of the results of this study were that the negotiation competencies for students can support careers in marketing so that it required the formation of assertiveness and an increase in self-efficacy in the learning process.